2011
DOI: 10.1111/j.1467-8624.2011.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Language Experiences in Preschool Classrooms and Children’s Kindergarten and Fourth-Grade Language and Reading Abilities

Abstract: Indirect effects of preschool classroom indexes of teacher talk were tested on fourth-grade outcomes for 57 students from low-income families in a longitudinal study of classroom and home influences on reading. Detailed observations and audiotaped teacher and child language data were coded to measure content and quantity of verbal interactions in preschool classrooms. Preschool teachers' use of sophisticated vocabulary during free play predicted fourth-grade reading comprehension and word recognition (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
325
4
30

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(371 citation statements)
references
References 62 publications
12
325
4
30
Order By: Relevance
“…While some have found that the impact of childcare (Colwell, Pettit, Meece, Bates & Dodge, 2001) and preschool interventions (Henning, McIntosh, Arnott & Dodd, 2010) may fade away over time, others have documented the preschool effects that are evident many years later (Dickinson & Porche, 2011 ;Snow et al, 2007 ;Vandell et al, 2010). Snow et al (2007) conducted a follow-up study on some of the children that participated in the Harvard Home-School study.…”
Section: Vocabulary Development During the Preschool And Elementary Ymentioning
confidence: 99%
See 2 more Smart Citations
“…While some have found that the impact of childcare (Colwell, Pettit, Meece, Bates & Dodge, 2001) and preschool interventions (Henning, McIntosh, Arnott & Dodd, 2010) may fade away over time, others have documented the preschool effects that are evident many years later (Dickinson & Porche, 2011 ;Snow et al, 2007 ;Vandell et al, 2010). Snow et al (2007) conducted a follow-up study on some of the children that participated in the Harvard Home-School study.…”
Section: Vocabulary Development During the Preschool And Elementary Ymentioning
confidence: 99%
“…Taken together, these studies suggest that young children who experience rich caregiver talk (in both amount and diversity) are likely to develop stronger language capacities themselves. Extended discourse during book-reading and play, in particular, seems to encompass and encourage the development of a rich and complex language (Dickinson & Porche, 2011 ;Zucker, Justice, Piasta & Kaderavek, 2010). Furthermore, children who are in the early stages of acquiring vocabulary may learn new labels by overhearing third-party conversations if they strategically orient to and monitor the conversation (Martínez-Sussmann, Akhtar, Diesendruck & Markson, 2011).…”
Section: Vocabulary Development During the Preschool And Elementary Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive information from this research indicates that a child's exposure to a full and varied vocabulary as early as age four is a powerful predictor of later literacy growth. Further, children with stronger language skills were more likely to engage in interesting conversations with their preschool teachers, and these conversations contributed favourably to children's ongoing literacy development (Dickinson & Porche, 2011).…”
Section: Vocabulary Developmentmentioning
confidence: 99%
“…Preschool education has an essential role for children, in terms of establishing a relationship between their written and oral language, vocal awareness, vocabulary, syntax and semantic skills. With early instrumentation, qualified preschool experiences affect school achievement by ensuring the improvement of verbal language skills and literacy skills (Dickinson & Porche, 2011). In the current study, it was observed that the participants started preschool education at the age of 3-4 and received preschool education of 2-3 years accordingly.…”
Section: Is There a Significant Relationship Between The Total Writinmentioning
confidence: 99%